Prolonged abstinence from cocaine or morphine disrupts separable valuations during decision conflict - Brian M. Sweis (Nature Portfolio, 2018)
Neuroeconomic theories suggest that conflict during decision, such as exhibited by relapsing drug addicts who continue drug use despite stated wishes not to, might arise from separable processes in decision making. Here the authors test mice in a foraging task designed to separate these processes and find that mice show alterations in separable components of decision conflict following abstinence from cocaine versus morphine.